Experimental Model of Skin Cryodestruction - Kovalov, Gennadiy O.; Vlasov, Oleksandr O.; Myroshnychenko, Mykhailo S.; Sandomirskiy, Boris P. (Problems of Cryobiology and Cryomedicine, 2019)
We suggest the in vivo experimental model of skin cryodestruction, suitable for studying the processes, occurring after skin neoplasm cryosurgery. To develop the model we have used low-temperature exposure using a cryoprobe, providing the temperature below the tissue cryoresistance threshold in the area of contact between the applicator working surface and skin. The initiation of destructive and inflammatory processes, both local and systemic, was observed in this model. Local morphological manifestations corresponded to the first phase of woundâ€“healing process. We noted the destructive and inflammatory signs accompanied by primary necrosis (due to direct thermal damage), and a leukocyte bank and secondary necrosis (resulting from hemodynamic disorders). The reparative processes in injured tissues were manifested in developed granulation tissue. At a system level, the tissue cryodestruction was accompanied by the oxidative stress development (an increased content of lipid peroxidation products, a suppressed enzymatic component of antioxidant defense system) and an increased content of cerulloplasmin and C-reactive protein in blood serum. Probl Cryobiol Cryomed 2019; 29(1): 088â€“101 Â